DISCLOSURE PRACTICES CONCERNING CONSOLIDATED FINANCIAL STATEMENS OF ROMANIANS GROUPS OF ENTITES - TIRON TUDOR ADRIANA (Annals of the University of Oradea: Economic Science, 2010)
The main object of this paper is to examine accounting harmonization in a sample of companies with regard to the presentation of consolidated financial statements. The results of the study indicate that listed firms tend to comply with IFRS requirements